Garré's osteomyelitis: a case report. - Ferreira, B. A.; Barbosa, A. L. (My University, 1992)
This is a case report of Garré's osteomyelitis caused by infection from a lower left molar which was successfully managed by root treatment following several unsuccessful attempts with antibiotic therapy alone. After 18 months there was complete resolution of the bony lesion.
Keywords: adolescent; case report; endodontics; female; foreign body; human; jaw disease; osteomyelitis; periostitis; tooth periapical disease; Adolescent; Case Report; Female; Foreign Bodies; Human; Mandibular Diseases; Osteomyelitis; Periapical Abscess; Periostitis; Root Canal Therapy